Reading Strategies of English Education Department Students of Universitas Muhammadiyah Yogyakarta - Parmiyanti (PBI 15 UMY 074, 2015)
*74 Reading is one of the four skills which highly needed by the students as independent learners to achieve the improvements in their learning process. In reading, students generally faced the various problems in order to get the meaning intended. This research aims to identify the problems encountered and the strategies used by English Education Department students of UMY in reading academic texts. The research used a qualitative research design by using an interview as the instrument. The participants of the research were six students. The findings showed that there were eight problems encountered by EED of UMY. They were unfamiliar vocabulary, technical vocabulary, idioms, word that has several meanings, complex sentences, knowledge of the topic and students’ habit. Related to the strategies, the students employed fourteen strategies. They are associating, using imagery, semantic mapping, structure reviewing, repeating, practicing naturally, getting the idea quickly, using resources, taking notes, summarizing, highlighting, using linguistic clues or other clues, identifying the purpose of a language task, asking question for clarification or verification. To summarize, the students of English Education Department of UMY, batch 2013, 2011, and 2010 still found that comprehending the English reading academic text is challenging because they still faced problems in reading English text even they have employed the strategies in comprehending the text. Based on finding, the students used cognitive strategy, memory, compensation, metacognitive and social strategy in comprehending the reading text. The most strategies that are used by the students are cognitive strategies. They employed seven cognitive strategies. Then memory strategies there are four memory strategies used by the students. They also employed compensation, metacognitive and social strategies.